2013
DOI: 10.1097/aog.0b013e318293d70b
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis of Term Amniotic Fluid Cell-Free Fetal RNA

Abstract: Objective To identify the tissue expression patterns and biological pathways enriched in term amniotic fluid (AF) cell-free fetal RNA by comparing functional genomic analyses of term and second trimester AF supernatants. Methods This was a prospective whole genome microarray study comparing eight AF samples collected from eight women at term who underwent prelabor cesarean delivery and eight second trimester AF samples from routine amniocenteses. A functional annotation tool was used to compare tissue expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
3
27
2
Order By: Relevance
“…We have capitalized on the abundance of these AFS transcripts to characterize normal fetal development (Hui et al 2012a(Hui et al , 2013a while performing discovery-driven research into the developmental underpinnings of several common genetic and nongenetic diseases, each of which will be explored here (Fig. 2, Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have capitalized on the abundance of these AFS transcripts to characterize normal fetal development (Hui et al 2012a(Hui et al , 2013a while performing discovery-driven research into the developmental underpinnings of several common genetic and nongenetic diseases, each of which will be explored here (Fig. 2, Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that the population of cffRNA present in AFS is affected by the sex and GA of the fetus. Outside the scope of this review, additional work has since been undertaken, which reveals marked differences between gene expression in the second and third trimesters of euploid fetal life (Hui et al 2013a). …”
Section: Studies In the Developing Fetusmentioning
confidence: 99%
“…Whole-genome microarray has been the most commonly used technique to examine the global RNA expression profile. Separate arrays exist for genomes from humans (Hui et al 2013; Edlow et al 2014), mice (Mischke et al 2013), and rats (Shankar et al 2011; Borengasser et al 2013). Functional analysis of the fetal transcriptome via bioinformatics resources such as gene set enrichment analysis (GSEA), database for annotation, visualization and integrated discovery (DAVID), and ingenuity pathways analysis (IPA), and others can highlight particular pathways, biological functions, or physiological systems that are dysregulated in a condition of interest, such as maternal obesity.…”
Section: Molecular Approaches Used In the Study Of Maternal Obesitymentioning
confidence: 99%
“…This did not detract from the studies ability to determine the presence of LPCAT1 mRNA in amniotic fluid as part of the human fetal transcriptome. These findings contribute to a growing body of knowledge describing novel information about human fetal development [7,8] .…”
Section: Discussionmentioning
confidence: 85%